1995
DOI: 10.1002/eji.1830251247
|View full text |Cite
|
Sign up to set email alerts
|

Default development of cloned human naive CD4 T cells into interleukin‐4‐ and interleukin‐5‐producing effector cells

Abstract: It was recently demonstrated that naive human and mouse CD4 T cells release low but sufficient levels of interleukin (IL)-4 at priming to support their development into IL-4 producers. To determine whether this IL-4 is produced by a minor subset of cells, freshly isolated human naive CD4 T cells were directly cloned by limiting dilution in the absence of exogenous IL-4. More than 95% of neonatal and 60% of adult naive T cells seeded in single-cell cultures could be expanded upon stimulation with anti-CD3 mAb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Briefly, the priming was performed in the presence of 100 ng/ml PHA (Murex Diagnostics, Chatillon, France) and irradiated CD32-B7 transfected fibroblasts (20). The feeder cells were added in the final density of 1 ϫ 10 6 cells/ml.…”
Section: Validation Of the Oligonucleotide Array Resultsmentioning
confidence: 99%
“…Briefly, the priming was performed in the presence of 100 ng/ml PHA (Murex Diagnostics, Chatillon, France) and irradiated CD32-B7 transfected fibroblasts (20). The feeder cells were added in the final density of 1 ϫ 10 6 cells/ml.…”
Section: Validation Of the Oligonucleotide Array Resultsmentioning
confidence: 99%
“…Although IL-4-independent signaling pathways have been described [2], IL-4 is the most critical parameter for the development of Th2 cells in mice, as well as in humans [1,2]. Studies in mice and humans indicate that naive T cells might produce IL-4 at very low levels [12][13][14][15][16][17][18][19]; however, it is not well understood how these T cells can utilize IL-4 so efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, like in the murine system, IL-4 seems to be the major factor required for the development of Th2 cells [11,12]. Despite the fact that human naive T cells, like their murine counterparts [13], produce either no or very low levels of IL-4 [12,[14][15][16][17][18][19], they sufficiently utilize these minute amounts of IL-4, suggesting that their IL-4R signaling machinery is highly efficient. On the other hand, murine T cells, once committed to the Th2 pathway, do produce high amounts of IL-4, but are resistant to respond to IL-4 to increase their IL-4 production [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…IFN-␥ secretion in response to PHA has been shown to be barely detectable in infants Ͻ2 mo old and to be still significantly lower in 2-to 12-mo-old infants than in older children (7,15). Based on these in vitro findings and on results obtained with cloned naive neonatal CD4 ϩ T cells (27), it has been concluded that newborns are unable to develop efficient Th1-mediated responses in vivo and are instead heavily biased toward Th2 responses. Information on the in vivo development of Ag-specific Th function in infants is limited and virtually nonexistent for very young infants (around 2 mo).…”
Section: Discussionmentioning
confidence: 99%